In vitro identification of a stem cell population from canine hair follicle bulge region - Castro, Raquel V. G. de [UNESP] (2018)
Skin is an extensive and easily accessible organ possessing various cell types that are constantly renewed. Previous studies have suggested the presence of a stem cell niche at the bulge region of the hair follicle, which contains cells positive for CD200 and CD34. Thus, this study sought to identify these cell populations in canine skin cells using the following methods 1- collecting samples of adult and fetal skin and isolating and culturing these cells using a method of simple enzymatic digestion and 2-testing the cell cultures for CD200 and CD34 in vitro and comparing them with skin tissue samples (in situ). Immunofluorescence results were negative for both CD200 and CD34 in frozen and paraffin embedded tissue, whereas the analysis showed that cultured cells positive for CD34, CD200 and double positive cells could be visualized in different percentages. Additionally, the pluripotency marker OCT4 was positive in the isolated cells. Analysis of CD34, CD200 and OCT4 by RT-qPCR showed that there is expression in fetal and adult cells, although no difference was observed between groups. Our results suggest that bulge stem cells from both fetuses and adult dogs were reported with the use of CD34 and CD200 markers in this study, and further techniques for cell isolation and in vitro cultivation are needed in order to obtain enriched populations of skin stem cells in dogs.